Pengaruh Program Keluarga Harapan Terhadap Tingkat Kemiskinan di Desa Mamala, Kecamatan Leihitu, Kabupaten Maluku Tengah - Selay, Ainayyah A; Girsang, Wardis; Luhukay, Johanna M (Jurnal Agrosilvopasture-Tech, 2025)
This study aimed to determine the effect of PKH on the poverty level in Mamala Village. This research was conducted in Mamala Village, Leihitu Subdistrict, Central Maluku Regency, in February 2024. The sampling technique in this study used a simple random sampling technique, namely 60 respondents who were randomly selected, 30 PKH recipient respondents, and 30 non-PKH recipients. The data analysis method used in this research is a quantitative method using the Wilcoxon and Kruskal-Wallis. The results showed that the family hope program had an effect on improving the household income of PKH recipients.